The Impact of the COVID-19 Pandemic as a Mediator of Factors Influencing Business Digitalization on SMEs in East Java, Indonesia - Widayanto, Mutinda Teguh; Koeshardjono, R. Hery; Priantono, Seger; Febriyanti, Regita; Trifanto, Angel Agus (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
This study aims to determine the direct influence of factors that can drive business digitalization among SMEs (Small, and Medium Enterprises) and the indirect influence using the COVID-19 pandemic as a mediator in East Java, Indonesia. These factors include experience, education, and digital literacy. This research is quantitative, with samples taken from the northern, southern, western, and eastern regions of East Java Province. The sample size consists of 120 respondents selected using purposive sampling. Data were analyzed using the Smart PLS-4 application, following stages of outer model testing, inner model testing, and hypothesis testing. The results indicate that experience does not have a direct positive effect on business digitalization, while education and digital literacy both have a direct positive impact on business digitalization. In the indirect effect test with the COVID-19 pandemic as a mediating variable, it was found that experience, education, and digital literacy all have a significant positive impact on business digitalization when mediated by the COVID-19 pandemic. These findings can be utilized by policymakers to promote increased business digitalization, which will foster the growth of SMEs in East Java.